INTRODUCTION TO CLOUD COMPUTING (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
In todayâ€™s era every organization wants to implement Cloud Computing to fullfil their needs ofÂ  computing.The Cloud computing is a fastest growing area in every sector like IT industry ,Government organizations etc . The Cloud computing emerges as a new computing paradigm which aims to provide computation, software, data access, and storage services that do not require end-user knowledge of the physical location and configuration of the system that delivers the services. The intent of this paper is to have a review on cloud computing, its working ,its use in various sectors,deployment models and services.